Generation of longer 3′ cDNA fragments from massively parallel signature sequencing tags - Silva, Ana Paula M. (Oxford University Press, 2004)
Massively Parallel Signature Sequencing (MPSS) is a powerful technique for genome-wide gene expression analysis, which, similar to SAGE, relies on the production of short tags proximal to the 3′end of transcripts. A single MPSS experiment can generate over 10(7) tags, providing a 10-fold coverage of the transcripts expressed in a human cell. A significant fraction of MPSS tags cannot be assigned to known transcripts (orphan tags) and are likely to be derived from transcripts expressed at very low levels (∼1 copy per cell). In order to explore the potential of MPSS for the characterization of the human transcriptome, we have adapted the GLGI protocol (Generation of Longer cDNA fragments from SAGE tags for Gene Identification) to convert MPSS tags into their corresponding 3′ cDNA fragments. GLGI-MPSS was applied to 83 orphan tags and 41 cDNA fragments were obtained. The analysis of these 41 fragments allowed the identification of novel transcripts, alternative tags generated from polymorphic and alternatively spliced transcripts, as well as the detection of artefactual MPSS tags. A systematic large-scale analysis of the genome by MPSS, in combination with the use of GLGI-MPSS protocol, will certainly provide a complementary approach to generate the complete catalog of human transcripts.